2011
DOI: 10.1002/cjoc.201180397
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Effect of Strong Alkali on Lowering the Interfacial Tension of Oil/Heavy Alkylbenzene Sulfonates System

Abstract: Experimental studies were conducted to explore the fundamental mechanisms of alkali to lower the interfacial tension of oil/heavy alkylbenzene sulfonates (HABS) system. Sodium hydroxide was used as the strong alkali chemical to investigate the interfacial tension (IFT) of oil/HABS system. The influences of salt and alkali on the interfacial activity were studied by the measurement of interfacial tension and partition coefficient. Moreover, the alkali/surfactant solutions were measured by dynamic laser scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The sulfonate surfactant is one of the most important surfactants in the enhanced oil recovery (EOR) industry and has played an important role in chemical EOR in past decades. , Petroleum sulfonate as an anionic surfactant was successfully applied in the Loudon oil field, Illinois, in the 1960s . Since then, surfactants such as petroleum sulfonate as well as alkyl benzenesulfonate and olefin sulfonate have been widely used in enhanced oil recovery due to their good performances and economic advantages. Nanoparticle surfactants and interfacial active nanoparticles could contribute to reducing interfacial tension, forming pulse emulsification and wettability alteration in porous media, which have also gained attention for their potential applications in enhanced oil recovery. However, those surfactants are limited in applications to high salinity reservoirs due to their poor salt tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfonate surfactant is one of the most important surfactants in the enhanced oil recovery (EOR) industry and has played an important role in chemical EOR in past decades. , Petroleum sulfonate as an anionic surfactant was successfully applied in the Loudon oil field, Illinois, in the 1960s . Since then, surfactants such as petroleum sulfonate as well as alkyl benzenesulfonate and olefin sulfonate have been widely used in enhanced oil recovery due to their good performances and economic advantages. Nanoparticle surfactants and interfacial active nanoparticles could contribute to reducing interfacial tension, forming pulse emulsification and wettability alteration in porous media, which have also gained attention for their potential applications in enhanced oil recovery. However, those surfactants are limited in applications to high salinity reservoirs due to their poor salt tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylbenzene sulfonates are widely employed in EOR and the considerable researches have been carried out on their chemical synthesis, performance evaluation, and practical application [20][21][22][23][24][25][26][27]. According to the mentioned above, as an important factor to influence the effect of oil displacement, the analysis on the molecular structures of surfactant has attracted more and more interests.…”
Section: Introductionmentioning
confidence: 99%
“…The size of emulsified oil droplets were larger and the maximum syneresis rate was 68% when used with ethanolamine, which was 33% higher, compared to sodium carbonate solution. Li et al 24 investigated the performance of three types of organic alkali (methylamine, trimethylamine, triethylamine) on IFT. The results showed that, when only organic alkali or surfactant were used, they produced high IFT, while the combination solutions of organic alkali and surfactant (even in low concentration) showed synergism and therefore had low IFT.…”
Section: ■ Introductionmentioning
confidence: 99%